دور نظام إستخبارات التسويق الدولي في تطوير إستراتيجية المنتج – دراسة حالة شركات السيارات الأجنبية بالجزائر- - فيصل, دلال; نوري, منير (Recherches économiques et managériales; Vol. 21 (2017): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES, 2018)
هدفت هذه الدراسة إلى تحديد دور نظام إستخبارات التسويق الدولي في تطوير إستراتيجية المنتج للأسواق الدولية مع دراسة حالة شركات السيارات الأجنبية بالجزائر، لأن بيئ ة التسويق الجزائرية تعتبر بيئة أجنبية بالنسبة للشركات القادمة من بلدان أخرى، ما يحتم على هذه الشركات تطوير إستراتيجية منتجاتها مع المتغيرات المكونة لهذه البيئة من أجل النجاح والنمو فيها، ومن أهم القطاعات التي تشهد منافسة شديدة في السوق الجزائري هو قطاع السيارات ، وذلك نظرا للعدد الكبير للمتعاملين فيه، ما يجعل من المعلومات التسويقية ذات أهمية إستراتيجية بالنسبة الشركات الناشطة في هذا القطاع، وذلك من أجل المتابعة المستمرة للتغيرات الحاصلة في البيئة التسويقية والتكيف معها، وصياغة الإستراتيجية التسويقية المناسبة لها، وهو ما يوفره نظام الإستخبارات التسويقية في إطاره الدولي . الكلمات المفتاحية : نظام إستخبارات التسويق الدولي، المنتج الدولي، إستراتيجية تطوير المنتج ، الشركة الأجنبية . Abstract : This study aims to determine the role of international marketing intelligence system in product development strategy to international markets with the case of foreign companies in Algeria because Algerian market environment is considered as a foreign environment for companies came from other countries, which makes it imperative for these companies to develop its product strategy with varying constituents in this environment in order to succeed, and the most important areas where competition is intense in the Algerian market is the automotive sector due to the large number of dealers in it, which makes the relevant marketing information of strategic importance for companies active in the sector. Followed by to the ongoing changes in the environment marketing and adapt with them, and formulate an appropriate marketing strategy, which is provided by the marketing intelligence system in their international context. Key words: international marketing intelligence system, international product , product development strategy , the foreign company .